Cervical 7-Thoracic 3 Laminoplasty for Resection of Arteriovenous Malformation: 2-Dimensional Operative Video. Issue 5 (23rd November 2019) - Hendricks, Benjamin K; Spetzler, Robert F
Abstract: Symptomatic spinal arteriovenous malformations (AVMs) are most frequently associated with hypoperfusion of the spinal cord, either from venous congestion or vascular steal, and are less frequently associated with hemorrhage. This patient had a large cervicothoracic spinal AVM and presented with right hemibody sensory deficit with intact motor function. The AVM had significant preoperative mass effect on the dorsal spinal cord with cord signal change. Preoperative digital subtraction angiography demonstrated a left supreme intercostal feeding artery and left thyrocervical feeding artery, which was embolized preoperatively. A laminoplasty was performed from cervical 7 to thoracic 3 to allow for adequate visualization. The lesion demonstrated an intradural extramedullary presence, which made preservation of the pia mater paramount during the resection. The AVM was disconnected and removed in its entirety as determined by operative visualization and postoperative imaging. The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary. Used with permission from Barrow Neurological Institute, Phoenix, Arizona .